2014
DOI: 10.14207/ejsd.2014.v3n4p323
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Campus: Indoor Environmental Quality (IEQ) Performance Measurement for Malaysian Public Universities

Abstract: Indoor Environmental Quality (IEQ) for academic buildings is one of the key characteristics of a sustainable campus. The low conditions of IEQ performance can contribute to the sick building syndrome and cause discomfort to the building users. Furthermore, good performance of IEQ can contribute to a comfort and conducive learning and working environment. The purpose of this paper is to discuss on the IEQ performance measurement of academic buildings for public universities in Malaysia. This research involved s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Studies have consistently shown that Indoor Environmental Quality, which deals with thermal comfort, visual comfort, and indoor air quality, is critical in determining occupant comfort, productivity, and performance [22][23][24]. These three attributes are considered the most crucial factors in creating a conducive learning environment in a studio, as a comfortable environment is likely to enhance learning efficiency and outcomes.…”
Section: Studio Attributes Of Indoor Environmental Qualitymentioning
confidence: 99%
“…Studies have consistently shown that Indoor Environmental Quality, which deals with thermal comfort, visual comfort, and indoor air quality, is critical in determining occupant comfort, productivity, and performance [22][23][24]. These three attributes are considered the most crucial factors in creating a conducive learning environment in a studio, as a comfortable environment is likely to enhance learning efficiency and outcomes.…”
Section: Studio Attributes Of Indoor Environmental Qualitymentioning
confidence: 99%
“…It is given unfortunate that a lot of hospitals now serve as a source of disease infections for unsuspecting staff and patients alike (Bachrach et al, 2012;Eckelman & Sherman, 2016). This is as a result of unpaid attention to the built environment, the components of which include; -Lighting (Yusoff & Sulaiman, 2014).…”
Section: Components Of the Environment That Associates With Wellnessmentioning
confidence: 99%
“…Therefore, the building‐related symptoms (e.g., eye, nose or throat irritation, headache or fatigue, skin irritation or breathing problems) have caused increasing public and scientific concerns about IEQ for over 20 years (Mendell, ). However, although public concern increased, occupant knowledge and understanding of the significance of creating a healthy IEQ for buildings is still insufficient (Yusoff & Sulaiman, ). For instance, Sekizawa et al () found that many consumers still have limited knowledge about IEQ factors, such as the chemicals used indoors and outdoors.…”
Section: Theoretical Backgroundmentioning
confidence: 99%